Dose‐response relationship between World Trade Center dust exposure and hepatic steatosis. Issue 10 (30th July 2021) - Jirapatnakul, Artit; Yip, Rowena; Branch, Andrea D.; Lewis, Sara; Crane, Michael; Yankelevitz, David F.; Henschke, Claudia I.
Abstract: Background: The World Trade Center (WTC) attack exposed thousands of workers to toxic chemicals that have been linked to liver diseases and cancers. This study examined the relationship between the intensity of WTC dust exposure and the risk of hepatic steatosis in the WTC General Responders Cohort (GRC). Methods: All low‐dose computed tomography (CT) scans of the chest performed on the WTC GRC between September 11, 2001 and December 31, 2018, collected as part of the World Trade Center Health Program, were reviewed. WTC dust exposure was categorized into five groups based on WTC arrival time. CT liver density was estimated using an automated algorithm, statistics‐based liver density estimation from imaging. The relationship between the intensity of WTC dust exposure and the risk of hepatic steatosis was examined using univariate and multivariable regression analyses. Results: Of the 1788 WTC responders, 258 (14.4%) had liver attenuation less than 40 Hounsfield units (HU < 40) on their earliest CT. Median time after September 11, 2001 and the earliest available CT was 11.3 years (interquartile range: 8.0–14.9 years). Prevalence of liver attenuation less than 40 HU was 17.0% for arrivals on September 11, 2001, 16.0% for arrivals on (September 12, 2001 or September 13, 2001), 10.9% for arrivals on September 14–30, 2001, and 9.0% for arrivals on January 10, 2001 or later ( p  = 0.0015). A statistically significant trend of increasing liver steatosis was observed with earlier arrival times ( p  < 0.0001). WTC arrival time remained a significant independent factor for decreased liver attenuation after controlling for other covariates. Conclusions: Early arrival at the WTC site was significantly associated with increasing hepatic steatosis.